FOLFIRINOX as induction treatment in rectal cancer patients with synchronous metastases: Results of the FFCD 1102 phase II trial. (November 2018) - ,; Dahan, L.; Auby, D.; Khemissa, F.; Ghiringhelli, F.; Nguyen, S.; Bedjaoui, A.; Terrebonne, E.; Thaury, J.; Baconnier, M.; Bachet, J.B.; Lucidarme, O.; et al.
Abstract: Aim of the study: The optimal therapeutic strategy in patients with rectal cancer and synchronous unresectable metastases remains unknown. We evaluated the efficacy of FOLFIRINOX induction therapy in this setting. Patients and methods: Chemotherapy-naïve patients received at least 8 cycles of FOLFIRINOX. The primary end-point was the 4-month disease control (4 m DC) rate. Tumour responses were centrally reviewed and assessed by computed tomography scan for metastases (Response Evaluation Criteria in Solid Tumours criteria) and magnetic resonance imaging for rectal tumorus. With a Simon 2-stage design and a targeted (H1) 4 m DC > 75%, 65 patients were enrolled from July 2012 to February 2015: male, 78%; median age, 61 years; performance status, 0–1, 98%; liver metastases, 92%; ≥2 metastatic sites, 63%. Results: Fifty-six (85%) of the 65 patients received the 8 planned FOLFIRINOX cycles. The primary objective was achieved (4 m DC rate: 94%; 95% confidence interval [CI], 86.3–97.8). Primary tumour symptoms decreased from 72% at baseline to 10% at 4 months. Response rate was 86%, and a >70% primary tumour volume decrease was seen in 63% of patients. Forty-four patients (68%) had at least one grade 3 side-effect; no toxic deaths occurred. Median follow-up was 35.0 months (95% CI, 31.3–43.7). Median progression-free survival and overall survival were 10.9 m (95% CI, 8.8–12.9) and 33.4 m (95% CI, 22.6–38.2), respectively. Conclusion: Upfront FOLFIRINOX is feasible and allows good local and distant control. It therefore offers the opportunity to choose the best therapeutic strategy for each patient and to personalise treatment according to the local and distant efficacy results of this induction step. Trial registration: Clinicaltrials.gov, NCT01674309 . Highlights: Upfront treatment for rectal cancer with synchronous metastases remains discussed. Induction FOLFIRINOX is effective on primary tumours and on metastases. Induction FOLFIRINOX allows to control primary rectal tumour–relative symptoms. Induction chemotherapy allows all treatment options to be secondarily considered.